Undiagnosed chicken meat aspiration as a cause of difficult-to-ventilate in a boy with traumatic brain injury. - Mohd Ariff@Ghazali, Nazhan Afeef; Mazlan, Mohd Zulfakar; Mat Hassan, Mohd Erham; Seevaunnamtum, Praveena A/P; Wan Muhd Shukeri, Wan Fadzlina; Nik Mohamad, Nik Abdullah; Hassan, Shamsul Kamarulrujan; Jaalam, Kamarudin; Hassan, Mohamad Hasyizan; Che Omar, Sanihah; Nadarajan, Chandran; Mohamad, Irfan (Elsevier Respiratory Medicine, 2018)
Introduction: Bronchoscopy is a commonly used procedure in the context of aspiration in the Intensive Care Unit setting. Despite its ability to remove mucus plug and undigested gastric contents, aspiration of gastric content into the trachea is one of the most feared complications among anesthesiologist.